Cowpea (Vigna unguiculata) Water Relations, Growth, and Productivity as Affected by Salinity in Two Soils with Contrasting Mineralogies - Jaciane Rosa Maria de Souza; Lucas Yago de Carvalho Leal; Martha Katharinne Silva Souza Paulino; José Alfredo Nunes; Rafael Luís Silva de Medeiros; Monaliza Alves dos Santos; Cintia Maria Teixeira Lins; Valdomiro Severino de Souza Júnior; Bruce Schaffer; Edivan Rodrigues de Souza (Soil Systems)
Soil salinity affects crop growth and production, especially in arid and semi-arid regions of the world. The interactions between salt ions and soil particles vary depending on soil texture, mineralogy, and ion composition. The relationship between soil ions and particles and the effects of this interaction on crop plants remains underexplored. This study evaluated the plant water relations, growth, and yield of cowpea (Vigna unguiculata) as affected by the salinity of the irrigation water in two different soil types with varying weathering levels and contrasting mineralogies. The treatments consisted of six salinity levels based on the electrical conductivity (EC) of the irrigation water (0, 1.5, 3, 4, 5, 6.0, or 9 dS m−1) and were tested in Ultisol (well-weathered soil) and Alfisol (less-weathered soil). The experiment was conducted over 80 days with 4 repetitions. The results showed that the plant salinity tolerance, growth, and yield in response to salinity varied depending on the soil type. Irrigation with saline water exceeding an EC of 3 dS m−1 completely halted cowpea production in Ultisol, whereas in Alfisol, production ceased at an EC above 6 dS m−1. Although it accumulates more salts under saline irrigation, Alfisol promotes better cowpea growth and yield than Ultisol.